Multiresistente Bakterien: Antibiotikaverordnung und Reserveantibiotika - Kern, Winfried V. (DMW - Deutsche Medizinische Wochenschrift, 2018)
Ascertaining critical indications for antibiotics and rational prescribing can delay and minimize the spread of antibiotic resistance. Room for improvement lies in particular in a stricter indication, in shortening antibiotic treatment and in initiating more targeted therapies with narrow-spectrum drugs. Not all infections due to multidrug-resistant organisms require treatment with reserve drugs. Detailed susceptibility testing together with enhanced knowledge of pharmacokinetics and -dynamics are needed for adequate treatment decisions. There are some new drugs with interesting spectrum of activity in development. The problem of antimicrobial resistance in human medicine, however, must also be seen in the context of “One Health” interactions between various systems including environmental issues and food production.
Keywords: Antibiotika; Infektionskrankheiten; Multiresistenz; Reserveantibiotika